Identificando estrategias efectivas para combatir la desnutrición infantil en el Perú - Beltrán B., Arlette (2011)
In Peru one out of four children suffers chronic malnutrition and inequalities among different income quintiles are significant. The consequences of this situation are alarming: limits future capacities and productivity, has harmful effects on health, and perpetuates poverty across generations. Using a two stages least squares methodology, this research analyzes the causes of child malnutrition in Peru based in series of demand factors, such as health status and parents’ education, and supply factors such as sewerage infrastructure and Programa Integral de Nutrición (PIN) coverage. The results show child’s weight at birth, district’s malnutrition rate, rations of food provided by PIN, mother’s age and child’s gender are the most important determinants of child malnutrition. When considering wealth quintiles, for the two poorest ones, the floor material, access to potable water, sewerage, cleaner cooking fuel, and food intake variety are among the most important determinants of malnutrition. Finally, broadening the PIN program coverage is the most effective measure relative to its costs. However, other policies, such as increasing the number of nutritionists and health posts available per district should also be implemented.